Folklore, Branding, and Social Media: A Multifaceted Communication Approach to Marketing in Indonesia - Tedjakumala, Ingrid; Damayani, Ninis Agustini; Mulyana, Deddy; Perbawasari, Susie (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
This research examines in depth the complex relationship between folklore, branding and social media in Indonesia. Folklore, as an integral part of cultural heritage, has great potential in marketing communications, but this potential has not been fully explored in a modern context. This research will examine how folklore narratives, which are full of cultural values, local wisdom and the history of Indonesian society, can be adapted and integrated into digital marketing content. With the aim of creating brand stories that are not only informative, but also touch consumers' emotions, building a deeper sense of closeness and attachment. This research explores various storytelling formats—from visual content on social media to video campaigns—and how each format can reach different audiences. The case study used is Bangflo Coffee, a local coffee brand, which uses their Instagram account to reach technology-savvy millennials. By using storytelling as their Communication strategy, they use culture to build community, shared values, and brand loyalty. This research not only highlights the importance of emotional connections in navigating Indonesia's highly diverse and dynamic market, but also provides marketers with valuable insights into how to leverage the richness of folklore to create resonant and effective marketing campaigns. The findings of this research contribute to a deeper understanding of the role of folklore in branding in the digital era, especially in Indonesia.